Depresi sebagai Prediksi Kematian dalam 1 Tahun pada Pasien Hemodialisis - Langgeng Perdhana; Shofa Chasani; Siti Nuraini (Fakultas Kedokteran, Universitas Andalas, 2021)
Depression is a mental disorder that is often found in hemodialysis patients. Depression had bad effects on patients. The study that determines the relationship between depression and all-cause mortality risk in hemodialysis patients is debatable. Objectives: To determine the role of depression as a predictor factor of all-cause mortality within one year in hemodialysis patients. Methods: This cohort study was conducted from February to August 2020 at the hemodialysis unit of Roemani Muhammadiyah Hospital, Semarang. The inclusion criteria were undergoing hemodialysis ≥3 months, hemodialysis frequency twice a week, being willing to participate in this study, being able to communicate well, and there was no history of previous mental disorders. Meanwhile, those whose data were incomplete, transferred to another hemodialysis unit, HBSAg +, and had other stressors unrelated to hemodialysis or Chronic Kidney Disease (CKD) were excluded from this study. Depression was assessed using the Beck Depression Inventory-II questionnaire. The collected data was then analyzed using Kaplan Meier and Cox regression. Results: From 82 respondents, 20 (24,4%) respondents categorized into depression group and 62 (75,6%) respondents into non depression group. Cox Regression analysis showed that depression plays a role as a predictor factor of all-cause mortality within one year in hemodialysis patients (p value=0,007, and Hazard ratio=3,587). Conclusion: Depression plays a role as a predictor factor of all causes of mortality within one year in hemodialysis patients.Keywords: depression, hemodialysis, mortality, end-stage renal disease